2010
DOI: 10.3390/w3010047
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit Analysis of Water Footprints in the UK

Abstract: Abstract:The Water Footprint, as an indicator of water consumption has become increasingly popular for analyzing environmental issues associated with the use of water resources in the global supply chain of consumer goods. This is particularly relevant for countries like the UK, which increasingly rely on products produced elsewhere in the world and thus impose pressures on foreign water resources. Existing studies calculating water footprints are mostly based on process analysis, and results are mainly availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 22 publications
1
45
2
Order By: Relevance
“…For example, Feng et al [125] found that the consumption WF per person for London, UK, was 58% higher for direct water use and 79% higher for virtual water use than the national average. Feng et al [128] also found this for urban household's in the Yellow River basin identifying a 50% higher WF than rural households.…”
Section: Urban Scalementioning
confidence: 99%
See 2 more Smart Citations
“…For example, Feng et al [125] found that the consumption WF per person for London, UK, was 58% higher for direct water use and 79% higher for virtual water use than the national average. Feng et al [128] also found this for urban household's in the Yellow River basin identifying a 50% higher WF than rural households.…”
Section: Urban Scalementioning
confidence: 99%
“…The urban WF studies have been performed for Beijing, China [66,97,[121][122][123]; Milan [124]; London, UK [125]; as well as Berlin, Delhi, and Lagos in Germany, India, and Nigeria, respectively [69]. Hoff et al [69] found that Berlin imported more than 60% of its virtual water from abroad whereas the virtual water for the developing cities of Delhi and Lagos primarily came from domestic sources.…”
Section: Urban Scalementioning
confidence: 99%
See 1 more Smart Citation
“…They used a method based on bottom-up approach which combines water use in detailed descriptions of individual production process and in consumption. Since energy comes from domestic and external sources, both sources are factored into the computation (Okadero et al, 2014;Feng et al, 2011). Energy sector by its very nature is water intensive and this can be used by countries whose water resources are poor to decide on the energy production method to adopt which will not severely affect water availability for other economic and domestic uses.…”
Section: 'Opportunity Cost' Wf:-mentioning
confidence: 99%
“…Conversely, the top-down approach moves from the highest level to the lower level according to the boundaries of a defined system and subsystem [7]. The I-O model initially developed by Leontief [19], a top-down technique, has been extensively applied to assess VW and WF, as well as sectoral water use on a regional or national scale [20][21][22][23][24][25][26][27][28][29]. Due to the high level of aggregation, the I-O technique is not adept at providing detailed calculation of a specific technique or product [13].…”
Section: Introductionmentioning
confidence: 99%